2018
DOI: 10.1007/s10995-018-2605-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Vitamin B12 Supplementation on Cognitive Outcomes in South Indian Children: A Randomized Controlled Clinical Trial

Abstract: Objectives To examine the effects of oral maternal vitamin B12 supplementation during pregnancy and early lactation on cognitive development in children. Method We studied 218 children born to mothers enrolled in a placebo-controlled, randomized trial of vitamin B12 supplementation during pregnancy through 6 weeks post-partum. Cognitive functions were assessed at 30 months using the Bayley Scales of Infant Development- 3rd edition (BSID III). The association of maternal sociodemographic characteristics, matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 24 publications
1
41
0
2
Order By: Relevance
“…None of the pooled estimates were significant. Among follow-up studies of nutritional supplementation, the pooled effect sizes were 0·03 (95% CI -0·05 to 0·11; 6 studies) for LAZ or HAZ score, -0·08 (-0·19 to 0·02; 6 studies) for 58 Nahar et al 48 Nahar et al 48 Jeon et al 41 Rosado et al 15 Phuka et al 21 Marchal et al 84 Adu-Afarwuah et al 18 Hess et al 16 Hess et al 16 Hess et al 16 Luby et al 23 Vazir et al 72 Phuka et al 21 Schmidt et al 53 Nahar et al 48 Nahar et al 48 Black et al 45 Lind et al 32 Hallammaa et al 82 Stewart et al 22 Thomas et al 60 Luby et al 23 Adu-Afarwuah et al 18 Schmidt et al 53 Shafique et al 24 Faber et al 14 Hallammaa et al 82 Maleta et al 17 Black et al 12 Black et al 12 Colombo et al 43 Husaini et al 50 Nguyen et al 34 Vazir et al 72 Black et al 63 Aboud et al 26 Gladstone et al 61 Yousafzai et al 42 Hamadani et al 74 Stewart et al 22 Dewey et al 20 Nguyen et al 34 Dewey et al 20 Lees cognitive score, and -0·03 (-0·18 to 0·12; 6 studies) for motor score. Among follow-up studies of interventions promoting nurturing care and learning opportunities, the pooled effect sizes were 0·06 (95% CI -0·12 to 0·25; 5 studies) for LAZ or HAZ score and 0·15 (-0·07 to 0·36; 5 studies) for cognitive or mental scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the pooled estimates were significant. Among follow-up studies of nutritional supplementation, the pooled effect sizes were 0·03 (95% CI -0·05 to 0·11; 6 studies) for LAZ or HAZ score, -0·08 (-0·19 to 0·02; 6 studies) for 58 Nahar et al 48 Nahar et al 48 Jeon et al 41 Rosado et al 15 Phuka et al 21 Marchal et al 84 Adu-Afarwuah et al 18 Hess et al 16 Hess et al 16 Hess et al 16 Luby et al 23 Vazir et al 72 Phuka et al 21 Schmidt et al 53 Nahar et al 48 Nahar et al 48 Black et al 45 Lind et al 32 Hallammaa et al 82 Stewart et al 22 Thomas et al 60 Luby et al 23 Adu-Afarwuah et al 18 Schmidt et al 53 Shafique et al 24 Faber et al 14 Hallammaa et al 82 Maleta et al 17 Black et al 12 Black et al 12 Colombo et al 43 Husaini et al 50 Nguyen et al 34 Vazir et al 72 Black et al 63 Aboud et al 26 Gladstone et al 61 Yousafzai et al 42 Hamadani et al 74 Stewart et al 22 Dewey et al 20 Nguyen et al 34 Dewey et al 20 Lees cognitive score, and -0·03 (-0·18 to 0·12; 6 studies) for motor score. Among follow-up studies of interventions promoting nurturing care and learning opportunities, the pooled effect sizes were 0·06 (95% CI -0·12 to 0·25; 5 studies) for LAZ or HAZ score and 0·15 (-0·07 to 0·36; 5 studies) for cognitive or mental scores.…”
Section: Resultsmentioning
confidence: 99%
“…We calculated pooled effect sizes if at least five studies reported an intervention versus control group comparison in any category of intervention (eg, nutritional supplementation and promotion of responsive care and learning opportunities). We applied the same criterion to stratified 29 Ong et al 37 Jeon et al 41 Lind et al 31 Rosado et al 15 Oelofse et al 52 Nahar et al 48 Smuts et al 62 Husaini et al 50 Phuka et al 21 Maleta et al 17 Krebs et al 54 Bauserman et al 55 Faber et al 14 Hess et al 16 Dewey et al 20 77 Luby et al 23 Stewart et al 22 Gladstone et al 61 Lees et al 80 Hallamaa et al 82 Tomlinson et al 78 Tumwine et al 79 Dewey et al 20 Adu-Afarwuah et al 18 Ashorn et al 19 Zhang et al 59 Thomas et al 60 Gowachirapant et al 51 Hamadani et al 35 Jacobson et al 58 Schmidt et al 53 Hanieh 36 Zhu et al 56 Nguyen et al 34 Christian et al 40 Gonzalez-Casano 87 Tofail et al 49 In utero 3 6 9 12 15 18 Months Years 64 Nahar et al 48 Hamadani et al 70 Tofail et al…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Two intervention studies (60,61) reported an effect of B12 supplementation on offspring cognitive status at 9 months and 30 months of age in the context of a randomized controlled trial (Supplementary Table 8). In this trial, mothers were randomized to receive either 50mcg oral vitamin B12 supplementation or placebo from the 1 st trimester of pregnancy till 6 weeks postpartum.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…There is evidence that some vitamins and minerals, like vitamin B12, have a direct effect on brain development and function (19). A recent trial in India determined that children of mothers who received vitamin B12 supplementation in pregnancy had significantly higher scores on expressive language scores as compared to children of mothers who received placebo (20). There are also many indirect pathways through which micronutrients may potentially provide benefit, including increases in birthweight, reduction in risk of prematurity, and reductions in maternal and fetal inflammation that may subsequently influence child development (18, 21).…”
Section: Discussionmentioning
confidence: 99%